2023
DOI: 10.2196/46528
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Patient-Reported Outcome Collection and Documentation in Medical Music Therapy: Process-Improvement Study

Abstract: Background To measure the effectiveness of nonpharmacologic interventions delivered during clinical care, investigators need to ensure robust and routine data collection without disrupting individualized patient care or adding unnecessary documentation burden. Objective A process-improvement study was undertaken to improve documentation consistency and increase the capture of patient-reported outcomes (PROs; ie, stress, pain, anxiety, and coping) within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, these locations typically had low-patient-volume clinical operations. While real-time process monitoring was not conducted in this study, providing a comprehensive PRO collection training, managerial expectation, and monitoring process represents an important opportunity to unify administrative efforts to optimize and equalize collection across sites [ 38 , 39 , 44 ].…”
Section: 0 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these locations typically had low-patient-volume clinical operations. While real-time process monitoring was not conducted in this study, providing a comprehensive PRO collection training, managerial expectation, and monitoring process represents an important opportunity to unify administrative efforts to optimize and equalize collection across sites [ 38 , 39 , 44 ].…”
Section: 0 Discussionmentioning
confidence: 99%
“…2.4.1 Questionnaires. The numeric rating scale (NRS) is commonly used for measuring pain, stress, and anxiety in clinical practice [52][53][54] and research [44,48,51], with demonstrated validity across these constructs. Owing to its simplicity, ease of use across populations, focus on symptoms in the present moment, and generalizability across various age and education levels [52], the NRS was selected as the instrument of choice in the present study.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation